Expectation of students from their teachers in undergraduate Medical Education in selected Medical Colleges in Bangladesh (Bangladesh Journal of Medical Education, 2014)
Introduction: An important aspect in higher education consists in improving the quality of students outcomes. Infact, different factors influence these outcomes. Among these factors are the quality of teaching, material used and at the students' expectation of the institution. Part of this perception is reflected in what students expect from their teachers. It is fact that students' performance depends on teachers' exigencies, teachers' perception of students' expectations and how the teachers fit with these expectations. Methodology: It was a cross sectional type of descriptive study. Conducted in 3 medical colleges for one year (July 2012 to June 2013) with the aim to find out the expectations of students from their teachers in undergraduate medical education in Bangladesh. The total respondents were 353 students selected by convenience sampling from preclinical, para clinical and clinical departments of those medical colleges. Pre-tested, self administered, structured anonymous using English & Bengal, Questionnaire, with Likert scale was used for data Collection. Comparison of expectation level between male & Female students, among the medical colleges were done by applying unpaired test. Results: 353 medical students of three selected medical colleges participated in this study. Among them 52% were female & 48% were male and 94% were Muslim and 6% were Hindu. There were 30 statement on students' expectations. Respondent expressed their views as expected and highly expected in all the statements. Regarding teaching, Teacher will be sincere, knowledgeable, will conduct class with adequate preparation. Punctual, teaching time will be used properly and will give explanation & example for better understandings' 92-97% students expressed their view as expected and highly expected. In interpersonal relation & in using modern instructional materials by the teachers 92-98% students expressed expected and highly expected. It is revealed that expectation on this 30 statement, students expectations are very high. So it is significant to address these issues by the teachers and administrator. Conclusion: It is revealed in the study that expectation of students from the selected three Medical Colleges were similar and no significant variations were found, students started their journey in Medical education with some expectation but all expectations which might not be perfect. But the students' expectation which they had in the study was the reflection of all the students of under graduate medical education in Bangladesh. DOI: http://dx.doi.org/10.3329/bjme.v3i1.18590 Bangladesh Journal of Medical Education Vol.3(1) 2012: 12-17